Perancangan Aplikasi Penganalisis Kesehatan Keuangan Menggunakan Metode RGEC untuk Bank Umum Syariah - Ani Dianasari; Ade Ali Nurdin; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The growing digital world makes the basis of this research to lead to the world of Financial-Technology increasingly. Through this application, the aim is to be able to analyze the soundness of Islamic Commercial Banks so that the public, especially customers, investors, and scholars who understand the world of banking, see a comparison of the soundness of banks so that they can assess which banks are operating well through their financial turnover and which are not. This application does not only see comparisons in terms of financial performance through ratios, Composite Ratings, and Categories that are raised based on the applicable OJK Regulations, but also can bring up the ranking of each financial ratio, scoring bank values, and also rankings to see which bank The best general Shariah from the inputted data. Based on the process, the FinT application successfully runs according to the purpose of this research.